Metabolic Pathways Regulating Colorectal Cancer: A Potential Therapeutic Approach - Zafari, Nima; Velayati, Mahla; Damavandi, Sedigheh; Pourali, Ghazaleh; Mobarhan, Majid G.; Nassiri, Mohammadreza; Hassanian, Seyed Mahdi; Khazaei, Majid; Ferns, Gordon A.; Avan, Amir (Current Pharmaceutical Design, 2022)
Colorectal cancer (CRC) is one of the most prevalent cancers globally. Despite recent progress in identifying etiologies and molecular genetics as well as new therapeutic approaches, the clinical outcome of current CRC therapies remains poor. This fact highlights the importance of further understanding underlying mechanisms involved in colorectal tumor initiation and progression. Abnormal metabolic alterations offer an evolutional advantage for CRC tumor cells and enhance their aggressive phenotype. Therefore, dysregulation of cellular metabolism is intricately associated with colorectal tumorigenesis. This review summarizes recent findings regarding the CRC-related changes in cellular metabolic pathways such as glycolysis, tricarboxylic acid cycle, fatty acid oxidation, and mitochondrial metabolism. We describe the oncogenic signaling pathways associated with metabolic dysregulation during malignant transformation and tumor progression. Given the crucial role of metabolic pathway alterations in the pathogenesis of CRC, we provide an overview of novel pharmacological strategies for the treatment of CRC by targeting metabolic and signaling pathways.
Keywords: glucose metabolism